PERAN ORGANIZATION FOR SECURITY IN EUROPE (OSCE) DALAM MENANGANI KONFLIK DI UKRAINA TIMUR - Sigalingging, Andrew Mayson; Retnaningsih, Umi O. (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The purpose of this research is to analyze the role of the OSCE as an international organization that has the task of maintaining security and peace in the country of Ukraine which is experiencing a prolonged conflict, especially in the East Ukraine region. The conflict in Ukraine began after the fall of Ukrainian President Victor Yanucovych who was pro-Russian in 2014 which prompted Russia to illegally annex Crimea and was then followed by armed conflict between Pro-Russian separatists and Pro-Government parties. This conflict is getting bigger and longer because Russia provides support to the rebels and separatists. And this attracts the OSCE to play a role in resolving and reducing conflicts that occur.Â This research is analyzed with the perspective of neorealism which believes that the state is the dominant actor but does not rule out the role of non-state actors. This research is also guided by the role theory and concept of Security. The method used is a qualitative method with a descriptive model. The technique of collecting data in this research is through literature study from several journals, books, documents and websites.This study shows the results of the roles performed by the OSCE in dealing with the conflict in Ukraine. The participation of the OSCE's efforts are in the form of negotiations, holding conferences, forming a charter of agreements, sending special monitoring missions to monitor the dynamics of the conflict, supervising the presidential election as well as weapons and missions to assess human rights and minorities during the conflict. The forms of roles that the OSCE has carried out in Ukraine have worked well, although they cannot stop the conflict from continuing.Keywords: Ukraine, OSCE, Conflict, Crimea and Russia.